2010
DOI: 10.2353/jmoldx.2010.090105
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Detection of Epidermal Growth Factor Receptor and KRAS Genes Using the Smart Amplification Process Version 2 from Formalin-Fixed, Paraffin-Embedded Lung Cancer Tissue

Abstract: Recent evidence indicates that the presence of epidermal growth factor receptor (EGFR) or KRAS mutations in non-small cell lung cancer (NSCLC) can predict the response of the tumor to gefinitib. However, it is difficult to detect these mutations using formalinfixed , paraffin-embedded (FFPE) tissues because the fixation process and aging can damage the DNA. In this study , we describe our work in adapting the Smart Amplification Process version 2 (SmartAmp2) to detect EGFR or KRAS mutations in DNA extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…We previously reported that the SmartAmp2 assay effectively detects mutations in DNA extracted from formalinfixed paraffin-embedded (FFPE) tissue because of this method's ability to amplify quite short sequences (30). We believe that the advantages of PNA-clamp SmartAmp2, its rapid detection time and ability to detect mutations in FFPE tissue, will enable this method to be particularly useful in the treatment of outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the SmartAmp2 assay effectively detects mutations in DNA extracted from formalinfixed paraffin-embedded (FFPE) tissue because of this method's ability to amplify quite short sequences (30). We believe that the advantages of PNA-clamp SmartAmp2, its rapid detection time and ability to detect mutations in FFPE tissue, will enable this method to be particularly useful in the treatment of outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…SmartAmp2 assays can detect deletions in the EGFR exon 19, and a mutation (L858R) in the EGFR exon 21. Although various deletions have been reported in the EGFR exon 19, PNAclamp methods allow the detection of almost all types of known deletions in a single assay (16,17). The assay principles of SmartAmp2, including PNA-clamp methods, have been described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit monoclonal primary antibodies with specificity for the 15-bp deletion in EGFR exon 19; EGFReceptor (E746-A750del Specific) (6B6) XP™ Rabbit mAb (Cell Signaling Technology, Inc., Beverly, MA) were used (1:100) and IHC was performed according to the manufacturer's recommendations. For positive samples from IHC, a section slide of the tumor was divided into several pieces (the adenocarcinomatous and squamous cell carcinomatous components) and macrodissected for DNA extraction using the QIAamp DNA FFPE tissue kit (Qiagen) as described previously (16). Mutational analyses were performed on extracted DNA samples using SmartAmp2 and PNA-enriched sequencing.…”
Section: Mutant-enriched Assay For Egfr Exon 19 (Pna-enriched Sequencmentioning
confidence: 99%
“…Genomic DNA was extracted from a 3-5 mm cube of tumor tissue using a DNA Mini kit (Qiagen, Hilden, Germany) and subsequently diluted to a concentration of 20 ng/µl. KRAS and EGFR mutations in lung cancer tissue were analyzed by peptide nucleic acid-enriched sequencing, as previously described (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%